Development and validation of a model of motor competence in children and adolescents - Luz, C.; Rodrigues, L. P.; Almeida, G.; Cordovil, R. (Journal of Science and Medicine in Sport, 2016)
Objectives: This study was aimed at developing a quantitative model to evaluate motor competence (MC) in children and adolescents, to be applicable in research, education, and clinical contexts. Design: Cross-sectional. Methods: A total of 584 children (boys n = 300) with ages between 6 and 14 years were assessed using nine well known quantitative motor tasks, divided into three major components (stability, locomotor and manipulative). Structural equation modelling through EQS 6.1 was used to find the best model for representing the structural and measurement validity of MC. Results: The final MC model was composed by three latent factors closely related with each other. Each factor was best represented by two of the initial three motor tasks chosen. The model was shown to give a very good overall fit (?2 = 12.04, p = .061; NFI = .982; CFI = .991; RMSEA = .059). Conclusions: MC can be parsimoniously represented by six quantitative motor tasks, grouped into three interrelated factors. The developed model was shown to be robust when applied to different samples, demonstrating a good structural and measurement reliability. The use of a quantitative protocol with few, simple to administer and well known, motor tasks, is an important advantage of this model, since it can be used in several contexts with different objectives. We find it especially beneficial for physical educations teachers who have to regularly assess their students.